Sustainability assessment of a Flemish office building with Level(s): a Level 1 assessment. (August 2019) - Ramon, D; Pironnet, C; Allacker, K
Abstract: Recently, Level(s) has been developed by the European Commission as a common EU framework to assess sustainability of buildings with the intention to provide a consistent and comparable framework across national boundaries. It aims at providing a general language for sustainability for buildings and to promote life cycle thinking. This paper describes the application and results of a Level 1 assessment for the design stage of a Flemish office building. Level 1 is a common performance assessment which aims to be used amongst others by building professionals. Common standards and simplified methods are used for the indicators. The paper focusses on the experiences of testing the method by evaluating the user-friendliness of the assessment method for architects considering the information and calculations needed. The added value of applying the methodology in the design stage is furthermore discussed. Based on the test phase, further improvement is recommended by aligning current national tools for data gathering and by providing default values. A Level 1 assessment allows to gain insights in various performances of a building but does not aim to evaluate the "sustainability" level. A level 2 assessment is probably more useful for practitioners to make well-founded choices between different design options.